A Quantitative Study of Network Robustness in Resting-State fMRI in Young and Elder Adults - Gomez-Ramirez, Jaime; Li, Yujie; Wu, Qiong; Wu, Jinglong (Frontiers in Aging Neuroscience, 2016)
Brain connectivity analysis have shown great promise in understanding of how aging affects functional connectivity, however, an explanatory framework to study healthy aging in terms of network efficiency is still missing. Here we study network robustness i.e., resilience to perturbations, in resting state functional connectivity networks (rs-fMRI) in young and elder subjects. We apply analytic measures of network communication efficiency in the human brain to make reasonable guesses about compensatory mechanisms elicited in aging. Specifically, we quantify the effect of "lesioning" (node cancelling) of either single regions-of-interest (ROI) or whole networks on global connectivity metrics (i.e., efficiency). We find that young individuals are more resilient than old ones to random "lesioning" of brain areas, global network efficiency is over 3 times lower in older subjects relative to younger subjects. On the other hand, the "lesioning" of central and limbic structures in young subjects yield a larger efficiency loss than in older individuals. Overall our study shows a more idiosyncratic response to specific brain network "lesioning" in elder compared to young subjects, and that young adults are more resilient to random deletion of single nodes compared to old adults.